Bacterial Community Profiling of Tropical Freshwaters in Bangladesh - Azmuda, Nafisa; Fakruddin, Md.; Khan, Sirajul Islam; Birkeland, Nils-Kåre (Frontiers in Public Health, 2019)
Seasonal and spatial variations in the bacterial communities in two tropical freshwater sources in Bangladesh, Lake Dhanmondi in central Dhaka and a pond in the outskirts of Dhaka, were assessed and compared using PCR-DGGE and deep sequencing of 16S rRNA genes as well as heterotrophic enrichments using water samples collected at nine different time points during one year. Temporal and spatial variations of common aquatic bacterial genera were observed, but no clear seasonal variations could be depicted. The major bacterial genera identified from these two sites were members of the Proteobacteria, Cyanobacteria, Actinobacteria, Bacteroidetes, Chlorobi, Chloroflexi, Verrucomicrobia and Firmicutes. Among the proteobacterial groups, members of the α-, β- and γ- Proteobacteria predominated. γ- Proteobacteria belonging to the Escherichia coli/ Shigella group even the diarrheagenic pathotypes of E. coli e.g. EPEC and ETEC were detected in most samples throughout the year, with no apparent correlations with other microbial groups. The other pathotypes, EHEC, EAEC and EIEC/Shigella spp. were also detected occasionally. This study represents the first thorough analysis of the microbial diversity of tropical freshwater systems in Bangladesh.